Linking Responsible Leadership and Green Innovation: The Role of Knowledge Sharing and Leader-Member Exchange - Huo, Chunhui; Safdar, Muhammad Arslan; Akhtar, Muhammad Waheed; Ahmed, Misbah (Frontiers in Environmental Science, 2022)
This study aims to explore how to encourage employees to engage in green innovation (GI). Drawing upon social learning theory, a moderated mediation model was theorized and tested to determine how responsible leadership triggers GI in fostering knowledge sharing. Additionally, two critical processes were distinguished by introducing leader-member exchange (LMX) as a moderator. A multi wave study collected from 228 employees from hospitality sector organizations generally supported the predictions. Specifically, responsible leadership was a significant predictor of GI. Moreover, LMX strengthened knowledge sharing mechanisms and attenuated the relationship between responsible leadership and GI. The findings and the theoretical underpinning of this study shed new light on GI in a responsible way that shapes knowledge sharing among organizational members and provides practical implications for leaders determined to improve environmental sustainability in organizations.